2019
DOI: 10.1016/j.dadm.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation after Surgery for Elders (RISE) study: Study design, procedures, and cohort profile

Abstract: Introduction The Role of Inflammation after Surgery for Elders study correlates novel inflammatory markers measured in blood, cerebrospinal fluid (CSF) assays, and [11C]‐PBR28 positron‐emission tomography imaging. Methods This study involved a prospective cohort design with patients who underwent elective hip and knee arthroplasty under spinal anesthesia. Sixty‐five adults participated with their family members. Inflammatory biomarker assays were measured preoperatively on day 1 and postoperatively at one mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…The inflammation factors and inflammatory cells are usually at high levels in people who have ever received surgery. Neuroinflammation happens more easily in stress situations and leads to the impairment of cognitive function [30]. The neuroinflammatory mechanism of POCD includes several aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation factors and inflammatory cells are usually at high levels in people who have ever received surgery. Neuroinflammation happens more easily in stress situations and leads to the impairment of cognitive function [30]. The neuroinflammatory mechanism of POCD includes several aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative delirium provides a unique clinical setting because we know exactly when inflammatory processes begin as the elective surgical procedures are typically scheduled weeks to months in advance. 106 and ASCRIBED (the impact of Acute SystematiC inflammation upon CSF and blood BiomarkErs of brain inflammation and injury in dementia) 107 will provide large cohort data on immune biomarkers in orthopedic patients during aging and ongoing neurodegeneration. These combined approaches are likely to contribute to a better understanding of delirium and AD pathology to refine therapeutic targets.…”
Section: Translational Potentialmentioning
confidence: 99%
“…The overall design and protocol of the study have been described in detail elsewhere ( Hshieh et al, 2019 ), and will be briefly reported here.…”
Section: Methodsmentioning
confidence: 99%
“…Total hip and knee arthroplasties were targeted because of their delirium risk and frequent use of spinal anesthesia ( Bruce et al, 2007 ), to avoid the potential confound of general anesthesia ( Hines et al, 2013 ). Exclusion criteria included any active psychiatric disorders, total blindness, and contraindication to spinal anesthesia/lumbar puncture, MRI, or [ 11 C]PBR28 PET (for details, see Hshieh et al, 2019 ). Importantly, all prospective patients were genotyped for the Ala147Thr polymorphism in the TSPO gene and those with predicted low-binding affinity for [ 11 C]PBR28 (Thr/Thr) ( Kreisl et al, 2013 , Owen et al, 2012 ) were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation